2005
DOI: 10.1371/journal.pmed.0020251
|View full text |Cite
|
Sign up to set email alerts
|

Up-Regulation and Profibrotic Role of Osteopontin in Human Idiopathic Pulmonary Fibrosis

Abstract: BackgroundIdiopathic pulmonary fibrosis (IPF) is a progressive and lethal disorder characterized by fibroproliferation and excessive accumulation of extracellular matrix in the lung.Methods and FindingsUsing oligonucleotide arrays, we identified osteopontin as one of the genes that significantly distinguishes IPF from normal lungs. Osteopontin was localized to alveolar epithelial cells in IPF lungs and was also significantly elevated in bronchoalveolar lavage from IPF patients. To study the fibrosis-relevant e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
421
3
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 432 publications
(447 citation statements)
references
References 48 publications
19
421
3
4
Order By: Relevance
“…55,56 Recently, it has also been shown that osteopontin-mediated alveolar epithelial cell migration and fibroblast migration and proliferation could be inhibited by an antibody to ␣ v ␤ 3 integrin. 57 These data confirm the results with a decrease in tubular epithelia-induced migration of macrophages and fibroblasts by S247.…”
Section: Discussionsupporting
confidence: 86%
“…55,56 Recently, it has also been shown that osteopontin-mediated alveolar epithelial cell migration and fibroblast migration and proliferation could be inhibited by an antibody to ␣ v ␤ 3 integrin. 57 These data confirm the results with a decrease in tubular epithelia-induced migration of macrophages and fibroblasts by S247.…”
Section: Discussionsupporting
confidence: 86%
“…Alveolar epithelial cells type II were positive for OPN in both diseases. Pardo et al 22 have previously shown that in IPF, mainly alveolar epithelial cells type II produce OPN. However, our findings clearly indicate that in PLCH and DIP macrophages also contribute to the increase in OPN production.…”
Section: Discussionmentioning
confidence: 97%
“…WISP-1 is a Wnt target gene that is overexpressed in lung fibrosis (Pardo et al 2005;Königshoff et al 2009). Furthermore, inhibition of WISP-1 attenuates the progression of fibrosis in vivo (Königshoff et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Certain components of the canonical Wnt/β-catenin signaling pathway have been reported to play a role in lung fibrosis, including Wnt-inducible signaling protein-1 (WISP-1) and frequently rearranged in advanced T cell lymphomas-1 (FRAT1, an inhibitor of GSK-3β-mediated phosphorylation of β-catenin) (Pardo et al 2005;Königshoff et al 2009). In addition, Gurung et al (2009) have shown that irradiation of human lung fibroblasts (HLFs) results in activation of Wnt/β-catenin signaling.…”
Section: Introductionmentioning
confidence: 99%